ANALYSIS OF BANK HEALTH LEVEL USING RGEC METHOD AT PT BANK NEGARA INDONESIA (PERSERO) Tbk - Purba, Arlina Pratiwi (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
This study aims to determine the health level of PT Bank Negara Indonesia (Persero) Tbk for the 2021-2023 period in terms of Risk profile, Good Corporate Governance (GCG), Earnings, Capital, and RGEC (Risk profile, GCG, Earnings, and Capital) as a whole. This type of research is quantitative using secondary data sources in the form of financial reports of PT Bank Negara Indonesia (Persero) Tbk for the 2021-2023 period. The data analysis technique used is bank health analysis with the Risk (Risk-based Bank Rating) RGEC approach. The results of the study show that during the 2021-2023 period: (1) The Risk Profile Aspect of PT Bank Negara Indonesia (Persero) Tbk for the 2021-2023 period was in a healthy condition with an average NPL value of 4.05%; 3.05%; 2.32% and LDR of 72.98%; 77.45% and 5% percent. The GCG aspect is in a healthy condition with a composite value of 2, (3) The Earnings aspect in the form of ROA and NIM is in the very healthy category with an average ROA value of 1.35%, 2.27% and 2.42%, and NIM of 5.5%; 6.22% and 5.87% with a very healthy category. The Capital aspect is in a very healthy condition with an average CAR value of 19.3%; 19.27% ​​and 21.95%. The RGEC aspect as a whole is in a Composite Ranking of 1, which is very healthy. The results of the study show that during 2021-2023 PT Bank Negara Indonesia (Persero) Tbk obtained a Composite Ranking (PK) of 1 or very healthy